Inter-donor variability of phase I/phase II metabolism of three reference drugs in cryopreserved primary human hepatocytes in suspension and monolayer. (June 2016) - den Braver-Sewradj, Shalenie P.; den Braver, Michiel W.; Vermeulen, Nico P.E.; Commandeur, Jan N.M.; Richert, Lysiane; Vos, J. Chris
Abstract: Cytochrome P450s (CYPs), UDP-glucuronosyltransferases (UGTs) and sulfotransferases (SULTs) are the most important enzymes for metabolic clearance. Characterization of phase I and phase II metabolism of a given drug in cellular models is therefore important for an adequate interpretation of the role of drug metabolism in toxicity. We investigated phase I (CYP) and phase II (UGT and SULT) metabolism of three drugs related to drug-induced liver injury (DILI), namely acetaminophen (APAP), diclofenac (DF) and tolcapone (TC), in cryopreserved primary human hepatocytes from 5 donors in suspension and monolayer. The general phase II substrate 7-hydroxycoumarin (7-HC) was included for comparison. Our results show that the decrease in CYP, UGT and SULT activity after plating is substrate dependent. As a consequence the phase I/phase II metabolism ratio is significantly affected, with a shift in monolayer towards phase I metabolism for TC and towards phase II metabolism for APAP and DF. Inter-donor variability in drug metabolism is significant, especially in sulfation of 7-HC or APAP. As CYP, UGT and SULT metabolism may lead to bioactivation and/or detoxification of drugs, a changed ratio in phase I/phase II metabolism may have important consequences for metabolism-related toxicity. Highlights: First comparison of phase I and phase II metabolism in cryopreserved human hepatocytes in suspension and monolayer Comparison of 7-HC metabolism as general UGT and SULT substrate with phase II metabolism of three DILI drugs Ratio of phase I/phase II metabolism of drugs is different in suspension and monolayer and donor-dependent. SULT-activity shows a high inter-donor variability, dependence on culture conditions, as well as on test substrate.